Blockade of reactive oxygen species and Akt activation is critical for anti-inflammation and growth inhibition of metformin in phosphatase and tensin homolog-deficient RAW264.7 cells. (December 2013) - Lin, Chiou-Feng; Young, Kung-Chia; Bai, Chyi-Huey; Yu, Bu-Chin; Ma, Ching-Ting; Chien, Yu-Chieh; Su, Hui-Chen; Wang, Hue-Yu; Liao, Chao-Sheng; Lai, Hsin-Wen; Tsao, Chiung-Wen
Abstract Context: Metformin is widely used for treatment of type 2 diabetes and has a potential application on the treatment of inflammation and cancer. Phosphatase and tensin homolog (PTEN) plays a critical role in cancer cell growth and inflammation; however, precise mechanisms remain unclear. Objective: We aimed to investigate the possible mechanisms of how PTEN regulates metformin against cell growth and inflammation. Materials and methods: We established PTEN knockdown in RAW264.7 murine macrophages (shPTEN cells) to detect inflammatory mediators using commercial kits, production of reactive oxygen species (ROS) by flow cytometry, cell growth by MTT assay and phosphorylated levels of signal molecules by western blot. Results: The shPTEN cells had a significant large amount of inflammatory mediators, such as inducible nitric oxide synthase (iNOS)/nitric oxide (NO) and cyclooxygenase-2 (COX-2)/prostaglandin E2 (PGE2); and also elevated the production of ROS and increased cell proliferation. These effects were accompanied with the activation of Akt and p38 mitogen-activated protein kinase (MAPK), and the inactivation of an AMP-activated protein kinase (AMPK) activator and extracellular signal-regulated kinase 1/2. Pretreatment with metformin not only blocked these inflammatory mediators, but also caused growth inhibition induced by significant apoptosis. Furthermore, inactivation of Akt, blockade of ROS generation and independence of activations of AMPK and MAPK by metformin were also observed. Conclusion: Macrophages with PTEN deficiency developed a continuous inflammatory microenvironment, which further aggravated tumor cell growth. Moreover, metformin affected PTEN-deficient cells dependent of inhibition of ROS production and Akt activation against enlarged inflammatory mediators and/or cell growth in shPTEN cells.